Pengaruh Kecerdasan Emosional terhadap Hasil Belajar PKn Siswa SMK IT Al Izhar Pekanbaru - Destri Armiza; Gimin Gimin; Supentri Supentri (Journal on Education, 2023)
This research is motivated by students who are lacking in intellect, but have the ability to manage emotions, understand emotions, motivate themselves, empathy and the ability to build relationships with others. Emotional intelligence is one of the internal factors that affect learning outcomes. This study aims to analyze the effect of emotional intelligence on the learning outcomes of Civics Students of SMK IT Al Izhar Pekanbaru. This type of research is descriptive quantitative using proportional random sampling technique with a population of 136 students of SMK IT Al Izhar Pekanbaru and a sample of 34 people. The results of the research from the documentation obtained the mean or average value of the odd midterm exam scores of students of SMK IT Al Izhar Pekanbaru Civics subject of 84.5 and the questionnaire was analyzed using simple linear regression with the regression equation Y = 9.651 + 0.772X. Based on the results of the F test obtained, namely Fhitung> Ftabel (122.497> 4.15) which means that there is an influence of Emotional Intelligence on Civics Learning Outcomes of Students of SMK IT AL Izhar Pekanbaru with R Square of 0.932. This means that the contribution of the influence between emotional intelligence on learning outcomes is 93.2%, while 6.8% (100-93.2%) is influenced by other variables not examined in this study. So the conclusion that there is a significant influence between emotional intelligence on the learning outcomes of Civics Students of SMK IT Al Izhar Pekanbaru.